SNAP‐Tag–Based Recombinant Photoimmunotherapeutic Agents for the Selective Detection and Killing of Light‐Accessible Melanotransferrin‐Expressing Melanoma and Triple‐Negative Breast Cancer - Suzanne Hippolite Magagoum; Fleury Augustin Nsole Biteghe; Gael Tchokomeni Siwe; Dirk Lang; Nkhasi Lekena; Stefan Barth (Cancer Medicine, 2025)
ABSTRACT Background Melanoma and triple negative breast cancer (TNBC) represent the most aggressive skin and breast cancer subtypes and are associated with poor diagnostic and limited therapeutic options leading to poor prognosis. Melanotransferrin/p97 (MTf), initially identified as a tumor‐associated antigen (TAA) in melanoma, is overexpressed in various solid tumors, including TNBC. Beyond its high differential expression and dreadful tumorigenic impact, MTf is also associated with chemoresistance development, and its inhibition significantly hampers tumor progression, making MTf a promising target for effective targeted therapies. Near‐infrared photoimmunotherapy (NIR‐PIT) is an approach that combines the precision of antibodies directed against specific TAA with the phototoxic effects of a light‐sensitive photosensitizer (IR700), activated by near‐infrared (NIR) light irradiation. This study aimed to generate a novel photoimmunoconjugate to specifically destroy MTf‐positive melanoma and TNBC cells in vitro following NIR light irradiation. Methods A single‐chain variable fragment (scFv) assembled from anti‐MTf antibody L49 was recombinantly fused with the SNAP‐tag protein (L49(scFv)‐SNAP), capable of irreversible and autocatalytic conjugation to any O(6)‐benzylguanine (BG) substrate in a 1:1 stoichiometry. Purified full‐length SNAP‐tag–based fusion protein (L49(scFv)‐SNAP‐tag) was either conjugated to a BG‐modified fluorescent imaging agent (Alexa 488) to specifically assess its selective binding to MTf‐expressing cell lines via confocal imaging and flow cytometry or to a BG‐modified light‐sensitive photosensitizer (IR700) to evaluate its phototoxic properties using an XTT cell viability assay. Results The selective binding and internalization of L49(scFv)‐SNAP‐Alexa 488 towards MTf‐positive melanoma and TNBC cell lines were successfully demonstrated with MTF expression percentages ranging from 52.8 to 83.1. Once confirmed, dose‐dependent phototoxicity of L49(scFv)‐SNAP‐IR700 was achieved on illuminated MTf‐positive cell lines showing IC50 values in the nanomolar range (2.20–5.24 nM). Conclusion This study highlights the therapeutic potential of MTf as a promising target for the diagnosis as well as selective and efficient elimination of NIR‐light‐accessible melanoma and TNBC by NIR‐PIT. Trial Registration NCT03769506